O uso da PCR em tempo real para o estudo da carga parasitária e dos níveis transcricionais durante a infecção experimental por Trypanosoma cruzi - Brígido, Rebecca Tavares e Silva (2016)
Trypanosoma cruzi is causative agent of Chagas disease, one of most neglected tropical diseases. Estimated that about 11 million people worldwide are infected by T. cruzi and about 6 to 7 million people are at risk in endemic areas. During the process of invasion of host and parasite interact enabling signal transduction and gene expression modulation in response to invasion. The diversity of activated proteins and pathways to repair the damage by disruption of the plasma membrane interest to us and thus present study developed a new form of detection and quantitation by polymerase chain reaction in real time (qPCR) of parasitic load T. cruzi and quantified transcriptional levels relative (RT-qPCR) of dysferlin, Sphingomyelin acid esferase (ASM), transcription factor EB (TFEB) Galectins 1 and 3 and Annexin A2. This study demonstrated that quantification by real time PCR using primers P21fw and P21rv was specific and sensitive for detection of T. cruzi in vivo and in vitro, as well as transcriptional levels of genes related to cytoskeletal organization and repair plasma membrane are modulated in response to damage generated by parasite.